Encephalitis with Infiltration by CD8+ Lymphocytes in HIV Patients Receiving Combination Antiretroviral Treatment. (18th March 2013) - Gray, Françoise; Lescure, François Xavier; Adle‐Biassette, Homa; Polivka, Marc; Gallien, Sébastien; Pialoux, Gilles; Moulignier, Antoine
Abstract We report the neuropathological findings in 10 HIV‐infected patients treated by combination antiretroviral therapy who developed subacute encephalopathy of rapidly progressive onset. Brain biopsy showed encephalitic lesions variably associated with myelin loss and slight axonal damage. There was inconstant, weak expression of HIV protein p24; tests for other pathogens were negative. The most striking feature was diffuse, perivascular and intraparenchymal infiltration by CD8+ T‐lymphocytes. Six patients improved after the treatment. Four had an unfavorable outcome and died within a year. Post‐mortem in one case confirmed HIV leukoencephalitis with p24‐positive multinucleated giant cells, associated with acute demyelinating encephalomyelitis (ADEM) in the cerebellum. There was diffuse infiltration by CD8+ lymphocytes; CD4+ cells were virtually absent. These cases may represent a specific clinicopathological entity, of which a few comparable cases have been already described. They can be included in the wide framework of immune reconstitution disease. Such syndromes have been described with opportunistic infections, but only seldom with HIV infection of the central nervous system (CNS). Our findings support the hypothesis that CD8+ cytotoxic lymphocytes can be harmful in immune reconstitution disease, particularly in the absence of CD4+ lymphocytes. CD8 cytotoxicity produces an acutization of a smoldering infection and/or an immunopathological reaction similar to ADEM.